Graph-based representation and reasoning : 22nd International Conference on Conceptual Structures, ICCS 2016, Annecy, France, July 5-7, 2016, Proceedings /: 22nd International Conference on Conceptual Structures, ICCS 2016, Annecy, France, July 5-7, 2016, Proceedings. (2016) - Unknown
No abstract available